Clinical Outcomes After Anterior Shoulder Stabilization in Overhead Athletes: An Analysis of the MOON Shoulder Instability Consortium. Issue 6 (May 2019) - Trinh, Thai Q.; Naimark, Micah B.; Bedi, Asheesh; Carpenter, James E.; Robbins, Christopher B.; Grant, John A.; Miller, Bruce S.; Ortiz, Shannon; Bollier, Matthew J.; Kuhn, John E.; Cox, Charlie L.; et al.
Background: Traumatic anterior shoulder instability is a common condition affecting sports participation among young athletes. Clinical outcomes after surgical management may vary according to patient activity level and sport involvement. Overhead athletes may experience a higher rate of recurrent instability and difficulty returning to sport postoperatively with limited previous literature to guide treatment. Purpose: To report the clinical outcomes of patients undergoing primary arthroscopic anterior shoulder stabilization within the Multicenter Orthopaedic Outcomes Network (MOON) Shoulder Instability Consortium and to identify prognostic factors associated with successful return to sport at 2 years postoperatively. Study Design: Case series; Level of evidence, 4. Methods: Overhead athletes undergoing primary arthroscopic anterior shoulder stabilization as part of the MOON Shoulder Instability Consortium were identified for analysis. Primary outcomes included the rate of recurrent instability, defined as any patient reporting recurrent dislocation or reoperation attributed to persistent instability, and return to sport at 2 years postoperatively. Secondary outcomes included the Western Ontario Shoulder Instability Index and Kerlan-Jobe Orthopaedic Clinic Shoulder and Elbow questionnaire score. Univariate regression analysis was performed to identify patient and surgical factors predictive of return to sport at short-term follow-up. Results: A total of 49 athletes were identified for inclusion. At 2-year follow-up, 31 (63%) athletes reported returning to sport. Of those returning to sport, 22 athletes (45% of the study population) were able to return to their previous levels of competition (nonrefereed, refereed, or professional) in at least 1 overhead sport. Two patients (4.1%) underwent revision stabilization, although 14 (28.6%) reported subjective apprehension or looseness. Age ( P = .87), sex ( P = .82), and baseline level of competition ( P = .37) were not predictive of return to sport. No difference in range of motion in all planes ( P > .05) and Western Ontario Shoulder Instability Index scores (78.0 vs 80.1, P = .73) was noted between those who reported returning to sport and those who did not. Conclusion: Primary arthroscopic anterior shoulder stabilization in overhead athletes is associated with a low rate of recurrent stabilization surgery. Return to overhead athletics at short-term follow-up is lower than that previously reported for the general athletic population.